Modern C++ for absolute beginners : a friendly introduction to C++ programming language and C++11 to C++20 standards - Dmitrović, Slobodan (Apress, 2020)
Learn the basics of the C++20 language from scratch, no experience necessary. You'll work with expressions and statements, variables, libraries, arguments, classes, functions, memory handling, and much more. Each section is filled with real-world examples, exceptions, and common mistakes to avoid. Modern C++ for Absolute Beginners will teach you more than just programming in C++20. It will provide you with a set of skills in computer science, which will serve you if you ever decide to deepen your knowledge in computer science or learn another programming language. The author will take you through writing a fully featured application for managing books in a big library. It will include users, encryption, database operations, a user interface, and more. Each chapter will add another layer to this program and by the end of the book the code will be complete and fully functional. You will work with C++20 features and standards, yet you will also compare and take a look into previous versions of C++. You will do so with plenty of examples and real code writing to gain an even better level of understanding. You will: Use the basics of C++: structures, variables, constants, ranges and lists, expressions, operators, and more Set up the Visual Studio development environment where you can write your own code Define functions, pointers, and references Discover object-oriented programming: classes and references, source location, objects, memory management, overflow, and more, using the most advanced C++ features Employ best practices in managing and controlling program workflow, multitasking, and more Program using lambda, modules, inheritance, polymorphism, smart pointers, templates, contracts, STL, concepts, and exceptions Debug your code to ensure your applications run as expected.